Merit students encyclopedia - Friedman, Emanuel; Halsey, William Darrach, 1918- (New York : Macmillan Educational Co ; London ; New York : Collier, 1982)
Encyclopedia entries are designed for students from fifth grade through high school and are written or reviewed by subject specialists
Includes bibliographies and index
1
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries